Pengabdian Kepada Masyarakat Melalui Peningkatan Kualitas Hidup Lansia Melalui Penerapan Pola Hidup Sehat Di Batam - Aprilya Sri Rachmayanti; Suhaera Suhaera; Ghalib Syukrillah Syahputra; Henny Rachdiati (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
The aging process is a natural phenomenon experienced by every individual, characterized by physical and mental changes that affect the body's functions and capabilities. The speed of the aging process can vary between individuals due to the influence of hormones and other factors. Elderly is often thought of as a disease, whereas aging is actually a natural process of decreasing the body's resistance to external and internal stimuli. During aging, the elderly experience physical, mental and psychological changes. Efforts to improve the health of older adults with chronic diseases are made through the adoption of a healthy lifestyle. This includes regular exercise programs, a healthy diet by limiting salt, fat, and cholesterol intake, quitting smoking, avoiding alcoholic beverages and caffeine, managing emotional stress, and undergoing regular monthly health check-ups. With age, older adults are at risk of various diseases, decreased body functions, imbalances, and the risk of falls. These challenges often conflict with older adults' desire to remain independent and active. The mismatch between expectations and conditions can even lead to depression. Therefore, there is a need for special attention to the health and well-being of the elderly with chronic diseases to maintain their quality of life.